Effect of sintering temperature on mechanical and electrical properties of lead-free Bi0.5(Na0.4K0.1)Ti0.98Zr0.02O3 piezoelectric ceramics - Pichitchai Butnoi (2019)
© 2019 Trans Tech Publications, Switzerland. Effect of sintering temperatures on phase formation. Mechanical and electrical properties of lead-free Bi0.5(Na0.8K0.2)0.5Ti0.98Zr0.02O3 or BNKTZ piezoelectric ceramics were investigated. The BNKTZ ceramics were prepared via a conventional solid-state sintering technique under various sintering temperature range 1100-1150°C for 2 h. The phase formation and microstructure of the ceramics were examined using X-ray diffraction (XRD) and scanning electron microscopy (SEM) method, respectively. XRD analysis indicated that all samples exhibited a single perovskite structure and no secondary phase. SEM microscopy study revealed an increase in grain size with increasing sintering temperature. The maximum values of density and maximum dielectric constant of the ceramics sintered at 1125 °C were 5.79 g/cm3 and 3446, respectively. In addition, the ceramics sintered at 1125 °C showed highest mechanical properties (HV = 4.32 GPa, HK = 5.87 GPa, E = 143 GPa and KIC = 1.30 MPa.m1/2). The highest values of ferroelectric and piezoelectric were found at this sintering temperature.